Conducción hopping en películas nanocristalinas del compuesto CZTSe usado como capa absorbente en celdas solares - Sena, N.; Departamento de Física, Grupo de Materiales Nanoestructurados, Universidad Nacional de Colombia - Bogotá, Colombia. (2014)
Here, we present electronic and transport properties of quaternary Cu2ZnSnSe4 (CZTSe) nanocrystalline films fabricated by physical co-evaporation. The samples were grown on soda-lime glass substrates and synthesis parameter ranges, Cu mass and substrate temperature were varied. Using thermopower at room temperature and spectral transmittance we found that the material is characterized by n-type conductivity and forbidden energy bandwidth of 1.7 eV, respectively. Electrical conductivity means (low temperature region; 90-200 K) showed that conductivity processes occur via variable range hopping between extended states. We obtained the parameters characterizing this mechanism, activation energy (Whopp), and range hopping (Rhopp), by employing the percolation theory and diffusion model. The density of defect states near the Fermi level of the material, N (EF) of the CZTSe samples is about 3,403x1018 cm-3 eV-1. We found a correlation between deposition parameters and electrical properties and observed a parameter influence on the formation of additional phases in the compound.